Vertical greenery systems (VGS) in urban tropics - Abdul-Rahman, -; Wang, C.; Rahim, A.M.; Loo, S.C.; Miswan, N. (Open House International Pub, 2014)
Numerous researchers proved Vertical Greenery System VGS beneficial to buildings and surroundings. However, it is still not widely applied in the tropics like Malaysia. This paper aims to determine the perceptions of VGS among the end users before it can be improved. A survey was conducted among 40 respondents, the end users of VGS in selected buildings within Klang Valley area. The collected data was analysed using statistical tests. From the findings, the primary benefits of VGS perceived by end users are enhancing visual quality, bringing nature harmony, reducing stress and reducing the urban heat island effects. The perceptions contradict with the results of ANOVA test between reducing the urban heat island effects and other VGS benefits that proves the need and effort to work on VGS in Malaysia.